Strengthening Marketing Strategies for Regional Public Service Agency (BLUD) State Vocational High Schools in West Sumatra through a Participatory Action Research Approach - Berri Brilliant Albar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2026)
The transformation of State Vocational High Schools (SMK Negeri) into Regional Public Service Agencies (BLUD) in West Sumatra Province provides institutional flexibility to commercialize student-led products and services. However, most SMKN BLUD units experience critical limitations in market positioning, commercial branding, and structured distribution channels, which leads to suboptimal revenue generation. This community service project aims to resolve these commercial barriers by delivering integrated business analysis and strategic marketing intervention through a provincial sharing session and adaptive mentoring framework. Utilizing a Participatory Action Research (PAR) approach across three structured cycles, the program engaged 43 SMKN school principals across West Sumatra in highly collaborative strategy formulations. The training focused on transitioning schools from conventional educational output mindsets toward professional market-driven orientation using corporate segmentation, targeting, positioning (STP), and the digital marketing mix. Quantitative evaluation via pre- and post-test instruments indicated a substantial 34.8% increase in participants' strategic comprehension (from a mean score of 62.1 to 83.7). Furthermore, the intervention successfully generated 43 preliminary digital marketing roadmaps and achieved a 92% participant satisfaction rate. In conclusion, embedding adaptive marketing strategies into vocational public service models effectively bridges the gap between educational innovation and market demand, creating a sustainable foundation for vocational financial independence.